Linguistic Landscapes im Ostseeraum: Transgressive Sticker in Greifswald und Turku - Linnasaari, Sanni; Kolehmainen, Leena (Finland, 2026)
This paper examines urban linguistic landscapes in two Baltic Sea cities, Greifswald in Germany and Turku in Finland. The focus is on transgressive stickers that appear on rubbish bins, lampposts, traffic signs, etc. Attached to diverse artifacts, the stickers serve various communicative purposes, such as promoting civil activism, taking a stand on current social issues, expressing identity and territory, and providing entertainment for passers-by. The data, consisting of over 800 stickers photographed in 2022–2023, were analyzed both quantitatively and qualitatively in terms of the languages and themes that appear on the stickers. The analysis shows that in both cities the discourses of the stickers are centered around the same themes, with the most popularthemes being anti-fascism, sport,and climate. However, the use of languages and the degree of multilingualism differ between the two cities. The choice of languages and their use on the stickers reflect the producers’attitudes towards different languages and the functions they consider them suitable for.
Keywords:linguisticlandscapes,transgressive stickers,Baltic Sea cities
Kulturen, Konvergenzen und Kommunikation: Begegnungen zwischen Finnland und dem deutschsprachigen Raum